Pengembangan Media Pembelajaran Perakitan Komputer Dengan Menerapkan Metode Agile Software Development - Aditya Ardi Nugraha; Faizatul Amalia; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Computers have become a major necessity in life now. Before the computer can be used the it must be assembled first. This process is called the process of assembling computer. This process requires special knowledge that is commonly found in computer assembly subjects in SMK. In the development of learning media, a lot of SMK that apply conventional media. This research is intended to implement and test computer learning media that has been developed. Development by using agile software development is expected to help develop learning media assembly of existing computer. Agile software development methods facilitate and provide space for learning media to be developed into broader direction, at its form as a medium of learning. Implementation of software is done by using Heroku as hosting server, Node JS as back-end server, and Firebase Auth and Database system as database server. According to the usability testing, the computer assembling learning media that has been developed by this research can be perceived by its users. Usability testing is measured at user perspective, system attitudes, technical quality, and information side resulting 75,5 as a score. According to cyclomatic complexity testing, learning media that have been developed results in low risk program category.